Cooperative Principle and Politeness in Children's Conversation in Dharma Wanita Kindergarten School Environment, Bengkulu Province) - Gumono, Gumono (Pusat Kajian Humaniora FBS Universitas Negeri Padang, 2022)
Language is a species-specific human capacity. Language is acquired gradually and simultaneously from birth. The purpose of this study was to find out a comprehensive description of forms and factors that influence the expression of acceptance and rejection of children's conversations in Dharma Wanita Kindergarten school, Bengkulu Province. A descriptive qualitative approach and ethnographic design were used in this study. The subjects of this study were children in the Dharma Wanita Kindergarten, Bengkulu Province. The researchers themselves are the key instrument. Data analysis shows that children in Dharma Wanita Kindergarten school can express personal attitudes in communicating. However, they have not fully applied the communicative principles (cooperative and politeness principle) in conversation, and any external factors influence their conversation.